A Distinct Pool of Nav1.5 Channels at the Lateral Membrane of Murine Ventricular Cardiomyocytes - Rougier, Jean-Sébastien; Essers, Maria C.; Gillet, Ludovic; Guichard, Sabrina; Sonntag, Stephan; Shmerling, Doron; Abriel, Hugues (Frontiers in Physiology, 2019)
Background: In cardiac ventricular muscle cells, the presence of voltage-gated sodium channels Nav1.5 at the lateral membrane depends in part on the interaction between the dystrophin-syntrophin complex and the Nav1.5 C-terminal PDZ-domain-binding sequence Ser-Ile-Val (SIV motif). α1-Syntrophin, a PDZ-domain adaptor protein, mediates the interaction between Nav1.5 and dystrophin at the lateral membrane of cardiac cells. Using the cell-attached patch-clamp approach on cardiomyocytes expressing Nav1.5 in which the SIV motif is deleted (SIV), sodium current (INa) recordings from the lateral membrane revealed a SIV-motif-independent INa. Since immunostainings have suggested that Nav1.5 is expressed in transverse (T-) tubules, this remaining INa might be carried by channels in the T-tubules. Of note, a recent study using heterologous expression systems showed that α1-syntrophin also interacts with the Nav1.5 N-terminus, which may explain the SIV-motif independent INa at the lateral membrane of cardiomyocytes. Aim: To address the role of α1-syntrophin in regulating the INa at the lateral membrane of cardiac cells. Methods and Results: Patch-clamp experiments in cell-attached configuration were performed on the lateral membranes of wild-type, α1-syntrophin knockdown, and SIV ventricular mouse cardiomyocytes. Compared to wild-type, a reduction of the lateral INa was observed in myocytes from α1-syntrophin knockdown hearts. Similar to SIV myocytes, a remaining INa was still recorded. In addition, cell-attached INa recordings from lateral membrane did not differ significantly between non-detubulated and detubulated SIV cardiomyocytes. Lastly, we obtained evidence suggesting that cell-attached patch-clamp experiments on the lateral membrane cannot record currents carried by channels in T-tubules such as calcium channels. Conclusions: Altogether, these results suggest the presence of a sub-pool of sodium channels at the lateral membrane of cardiomyocytes that is independent of α1-syntrophin and the PDZ-binding motif of Nav1.5, located in membrane domains outside of T-tubules. The question of a T-tubular pool of Nav1.5 channels, however, remains open.